Mechanistic insights into OC-COH coupling in CO2 electroreduction on fragmented copper - Yao,K; Li,J; Wang,H; Lu,R; Yang,X; Luo,M; Wang,N; Wang,Z; Liu,C; Jing,T; Chen,S; Cortes,E; et al. (Journal of the American Chemical Society, 2022)
The carbon–carbon (C–C) bond formation is essential for the electroconversion of CO2 into high-energy-density C2+ products, and the precise coupling pathways remain controversial. Although recent computational investigations have proposed that the OC–COH coupling pathway is more favorable in specific reaction conditions than the well-known CO dimerization pathway, the experimental evidence is still lacking, partly due to the separated catalyst design and mechanistic/spectroscopic exploration. Here, we employ density functional theory calculations to show that on low-coordinated copper sites, the CO bindings are strengthened, and the adsorbed CO coupling with their hydrogenation species, COH, receives precedence over CO dimerization. Experimentally, we construct a fragmented Cu catalyst with abundant low-coordinated sites, exhibiting a 77.8% Faradaic efficiency for C2+ products at 300 mA cm–2. With a suite of in situ spectroscopic studies, we capture an OCCOH intermediate on the fragmented Cu surfaces, providing direct evidence to support the OC–COH coupling pathway. The mechanistic insights of this research elucidate how to design materials in favor of OC–COH coupling toward efficient C2+ production from CO2 reduction.